Evaluation of the presence of VEGF, BMP2 and CBFA1 proteins in autogenous bone graft: Histometric and immunohistochemical analysis - Guskuma, Marcos Heidy; Vieira, Eduardo Hochuli [UNESP]; Pereira, Flávia Priscila; Rangel-Garcia Jr., Idelmo; Okamoto, Roberta [UNESP]; Okamoto, Tetuo; Filho, Osvaldo Magro (Elsevier, 2013)
Aims: The purpose of this study was to evaluate the expression of proteins that participate in the osteoinduction stage (VEGF, BMP2 and CBFA1) of the process of bone regeneration of defects created in rat calvariae and filled with autogenous bone block grafts. Materials and methods: 10 adult male rats (Rattus norvegicus albinus, Wistar) were used, who received two bone defects measuring 5 mm each in the calvariae. The bone defects constituted two experimental groups (n = 10): Control Group (CONT) (defects filled with a coagulum); Graft Group (GR) (defects filled with autogenous bone removed from the contralateral defect). The animals were submitted to euthanasia at 7 and 30 days post-operatively. Results: Quantitative analysis demonstrated significantly greater bone formation in Group GR, but the presence of the studied proteins was significantly greater in the CONT Group in both time intervals of observation. Conclusion: It was not possible in this study in cortical bone block groups to detect the osteoinductive proteins in a significant amount during the repair process. © 2013 European Association for Cranio-Maxillo-Facial Surgery.
Keywords: Bone Morphogenetic Protein 2; Bone transplant; Core Binding Factor Alpha 1 Subunit; Immunohistochemistry; Vascular Endothelial Growth Factor A